Application of metagenomic next-generation sequencing in patients with infective endocarditis - Li, Shao-Lin; Zhao, Xi; Tao, Jun-Zhong; Yue, Zhen-Zhen; Zhao, Xiao-Yan (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives Metagenomic next-generation sequencing (mNGS) technology is helpful for the early diagnosis of infective endocarditis, especially culture-negative infective endocarditis, which may guide clinical treatment. The purpose of this study was to compare the presence of culture-negative infective endocarditis pathogens versus culture-positive ones, and whether mNGS test results could influence treatment regimens for patients with routine culture-negative infective endocarditis. Methods The present study enrolled patients diagnosed with infective endocarditis and tested for mNGS in the First Affiliated Hospital of Zhengzhou University from February 2019 to February 2022 continuously. According to the culture results, patients were divided into culture-negative group (Group CN, n=18) and culture-positive group (Group CP, n=32). The baseline characteristics, clinical data, pathogens, 30 day mortality and treatment regimen of 50 patients with infective endocarditis were recorded and analyzed. Results Except for higher levels of PCT in the Group CN [0.33 (0.16-2.74) ng/ml vs. 0.23 (0.12-0.49) ng/ml, P=0.042], there were no significant differences in the basic clinical data and laboratory examinations between the two groups (all P>0.05). The aortic valve and mitral valve were the most involved valves in patients with infective endocarditis (aortic valve involved: Group CN 10, Group CP 16; mitral valve involved: Group CN 8, Group CP 21; P>0.05) while 9 patients had multiple valves involved (Group CN 2, Group CP 7; P>0.05). The detection rate of non-streptococci infections in the Group CN was significantly higher than that in the Group CP (9/18 vs. 3/32, P=0.004). There was no significant difference in patients with heart failure hospitalization and all-cause death at 30 days after discharge (3 in Group CN vs. 4 in Group CP, P>0.05). It is worth noting that 10 patients with culture-negative infective endocarditis had their antibiotic regimen optimized after the blood mNGS. Conclusions Culture-negative infective endocarditis should be tested for mNGS for early diagnosis and to guide clinical antibiotic regimen.